Stanford University Memorial Church - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows part of the facade of the Memorial Church at Stanford University. The stone plaque reads "Memorial Church erected by Jane Lathrop Stanford to the glory of God and in loving memory of her husband Leland Stanford."